Pengembangan Sistem Incident Management Web Menggunakan Waterfall Berdasarkan ITIL 4 untuk Meningkatkan Layanan TI Kampus - Muhamad Yafie Akmal; Nugroho Dwi Saputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Information technology (IT) services in higher education require consistent and standardized incident management; however, the Incident Management practices at the Information Technology and System Institute (LTSI) of STT Terpadu Nurul Fikri remain suboptimal. This is caused by inconsistent documentation and the absence of standards for incident logging, classification, and prioritization, resulting in an unstructured resolution process. This research aims to implement IT Service Management (ITSM) based on the ITIL 4 framework, particularly the Incident Management practice, to improve the quality of IT services at LTSI STT Terpadu Nurul Fikri. This study employed the Action Research method integrated with the Waterfall method for its software development. Data collection techniques included interviews, observation, and documentation studies, which were then analyzed using Gap Analysis and the Miles, Huberman, and Saldaña qualitative data analysis model. The results of the needs analysis were implemented into an Incident Management system built on the Laravel 12 framework. The system was subsequently evaluated through Black Box Testing and User Acceptance Testing (UAT) involving LTSI Admins and the academic community. The findings indicate that the implementation of ITIL 4 Incident Management produced a more structured service process through automated ticket logging, prioritization, resolution-status monitoring, and the establishment of a Knowledge Base/Known Error Database (KEDB). This is evidenced by the system functionality testing (Black Box Testing) achieving a 100% success rate, and the user acceptance testing (UAT) obtaining a 100% feasibility score, proving that the developed system is capable of enhancing IT service governance on campus.